Apolipoprotein A‐l improves pancreatic β‐cell function independent of the ATP‐binding cassette transporters ABCA1 and ABCG1. Issue 7 (10th April 2019) - Hou, Liming; Tang, Shudi; Wu, Ben J.; Ong, Kwok-Leung; Westerterp, Marit; Barter, Philip J.; Cochran, Blake J.; Tabet, Fatiha; Rye, Kerry-Anne
ABSTRACT: Apolipoprotein A‐I (apoA‐I), the main protein constituent of HDLs, increases insulin synthesis and insulin secretion in pancreatic β cells. ApoA‐I also accepts cholesterol that effluxes from cells expressing ATP‐binding cassette transporter A1 (ABCA1) and ATP‐binding cassette transporter G1 (ABCG1). Mice with conditional deletion of ABCA1 and ABCG1 in β cells [β‐double knockout (DKO) mice] have increased islet cholesterol levels and reduced glucose‐stimulated insulin secretion (GSIS). The project asks whether metabolic pathways are dys‐regulated in β‐DKO mouse islets and whether this can be corrected, and GSIS improved, by treatment with apoA‐I. β‐DKO mice were treated with apoA‐I or PBS, and islets were isolated for determination of GSIS. Total RNA was extracted from β‐DKO and control mouse islets for microarray analysis. Metabolic pathways were interrogated by functional enrichment analysis. ApoA‐I treatment improved GSIS in β‐DKO but not control mouse islets. Plasma lipid and lipoprotein levels and islet cholesterol levels were also unaffected by treatment with apoA‐I. Cholesterol metabolism, glucose metabolism, and inflammation pathways were dysregulated in β‐DKO mouse islets. This was not corrected by treatment with apoA‐I. In summary, apoA‐I treatment improves GSIS by a cholesterol‐independent mechanism, but it does not correct metabolic dysregulation in β‐DKO mouse islets.—Hou, L., Tang, S., Wu, B. J., Ong, K.‐L., Westerterp, M., Barter, P. J., Cochran, B. J., Tabet, F., Rye, K.‐A. Apolipoprotein A‐I improves pancreatic β‐cell function independent of the ATP‐binding cassette transporters ABCA1 and ABCG1. FASEB J. 33, 8479–8489 (2019). www.fasebj.org